The common player-avatar interaction scale (cPAX): Expansion and cross-language validation. Issue 129 (September 2019) - Banks, Jaime; Bowman, Nicholas David; Lin, Jih-Hsuan Tammy; Pietschmann, Daniel; Wasserman, Joe A.
Highlights: Player-avatar interactions (PAX) are central to videogaming experiences and effects. A PAX metric valid across languages would facilitate cross-cultural comparisons. A common solution is developed for English, traditional Chinese, German languages. One dimension is validated: anthropomorphic autonomy. Three dimensions are refined: relational closeness, critical concern, sense of control. Abstract: The connection between player and avatar is understood to be central to the experience and effects of massively multiplayer online (MMO) gaming experiences, and these connections emerge from the interplays of both social and ludic characteristics. The comprehensive social/ludic measure of this player-avatar interaction (PAX), however, features some dimensions with theoretical/operational gaps and limited reliability, and is available only in English (despite evidence of potential cultural variations in player-avatar relations). The present study aimed to a) enhance and refine the PAX metric, and b) translate and validate a common metric that bridges English, German, and traditional Chinese languages to facilitate future comparative research. Through exploratory factor analysis of data from MMO players in each of these language-based populations, an improved 15-item common Player Avatar Interaction (cPAX) scale is presented, with four dimensions: relational closeness, anthropomorphic autonomy, critical concern, and sense of control. The metric is shown to be reliable within and across populations, and construct validity tests show expected associations between scale dimensions and both player-avatar relationship types and senses of human-like relatedness.